OCCUPATIONAL BURNOUT AND PROFESSIONAL VALUES AMONG UNIVERSITY TEACHERS: GENDER AND INSTITUTIONAL DIFFERENCES - Kumar, Vijay; Joshi, Anuradha (International Journal For Research In Business, Management And Accounting, 2016)
The present study was conducted to study the occupational burnout and professional values of male and female teachers of government and private universities. Descriptive survey method has been used in the present study to obtain the pertinent and precise information. Purposive sampling technique was used for selection of sample of 200 University teachers. The data on occupational burnout and professional values was obtained by using Maslach Burnout Inventory and Professional Values scale. 2X2 factorial design of ANOVA is applies to analyze the data. The main finding of the study exhibits that (a) gender do not make any influence on occupational burnout and professional values of university teachers. (b) Institution type also does not make any influence on occupational burnout and professional values. (c) The interaction of institution type and gender also do not make any influence on occupational burnout and professional values.